1988
DOI: 10.1164/ajrccm/138.6.1519
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary Rehabilitation in COPD Patients with Elevated PCO2

Abstract: Exercise programs are a mainstay of pulmonary rehabilitation for COPD. COPD patients with elevated PCO2 are severely impaired and might benefit from rehabilitation more than other patients. However, there is no systematic data to indicate that hypercapnic COPD patients benefit from intensive rehabilitation. Indeed, in patients with hypercapnia, increased exercise might overtax respiratory muscles, which are weak relative to those of eucapnic patients. To investigate this issue, we reviewed all COPD patients ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0
1

Year Published

1995
1995
2009
2009

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(17 citation statements)
references
References 6 publications
1
15
0
1
Order By: Relevance
“…Later, lactic acid production was seen as a prerequisite to achieve an appropriate training response (34), as reductions in lactic acid were coupled to significant reductions of minute ventilation for a given work rate and oxygen consumption. However, more recent studies in which high-intensity training stimuli were applied clearly showed that patients with FEV 1 below 40% of the predicted values or those with hypercapnia (GOLD Stage IV) should not be excluded from exercise training (37,37,157,262,263). In a large study by Berry and coworkers (166), patients with mild, moderate, and severe COPD showed the same proportional improvement in exercise tolerance after pulmonary rehabilitation.…”
Section: Should Exercise Training Be Prescribed For All Patients Withmentioning
confidence: 99%
See 1 more Smart Citation
“…Later, lactic acid production was seen as a prerequisite to achieve an appropriate training response (34), as reductions in lactic acid were coupled to significant reductions of minute ventilation for a given work rate and oxygen consumption. However, more recent studies in which high-intensity training stimuli were applied clearly showed that patients with FEV 1 below 40% of the predicted values or those with hypercapnia (GOLD Stage IV) should not be excluded from exercise training (37,37,157,262,263). In a large study by Berry and coworkers (166), patients with mild, moderate, and severe COPD showed the same proportional improvement in exercise tolerance after pulmonary rehabilitation.…”
Section: Should Exercise Training Be Prescribed For All Patients Withmentioning
confidence: 99%
“…The variance explained by the proposed model, however, is too low to allow for appropriate patient selection. Older age (267), severe lung function impairment (166), the presence of hypercapnia (262), and current smoking (268) seem not to be valid exclusion criteria for pulmonary rehabilitation.…”
Section: Should Exercise Training Be Prescribed For All Patients Withmentioning
confidence: 99%
“…Whilst these two tests have provided useful information for patients with heart failure and chronic obstructive pulmonary disease, (Foster and Thomas 1990;Foster et al 1988;Guyatt et al 1989) the increase in heart rate obtained with both forms of walk test was only moderate with early MI patients, and the exercise prescription equivalent to 40% peak oxygen uptake was less than the resting heart rate.…”
Section: Discussionmentioning
confidence: 99%
“…69,70 Foster et al 69 found that patients with an elevated pCO 2 at rest will tolerate exercise training and can improve their functional status to an extent that approaches the improvement reported among eucapnic patients. Furthermore, the results of a nonrandomized concurrent cohort study, 70 in which the effect of rehabilitation in patients 75 years of age or older was compared with younger patients, supported the benefits of rehabilitation among the older population.…”
Section: Issues Specific To the Elderly Patient With Copdmentioning
confidence: 99%